Efficacy of therapeutic fasting and plant-based diet in patients with rheumatoid arthritis (NutriFast): study protocol for a randomised controlled clinical trial - Anika M Hartmann (BMJ Open)
Background Previous studies have shown beneficial effects of therapeutic fasting and plant-based dietary interventions on disease activity in patients with rheumatoid arthritis (RA) for a duration of up to 1 year. To date, the effects of such interventions on the gut microbiome and on modern diagnostic markers in patients with RA have not been studied. This trial aims to investigate the clinical effects of therapeutic fasting and a plant-based diet in patients with RA, additionally considering current immunological diagnostic tools and microbiome analyses.Methods/design This trial is an open-label, single-centre, randomised, controlled, parallel-group clinical trial. We will randomly assign 84 patients with RA under a stable standard therapy to either (1) therapeutic fasting followed by a plant-based dietary intervention or (2) to a conventional nutritional counselling focusing on an anti-inflammatory dietary pattern according to the recommendations of the Deutsche Gesellschaft für Ernährung (German society for nutrition). Primary outcome parameter is the group difference from baseline to 12 weeks on the Health Assessment Questionnaire (HAQ). Other secondary outcomes include established clinical criteria for disease activity and treatment response in RA (Disease Activity Score 28, Simple Disease Activity Index, ACR-Response Criteria), changes in self-reported health and physical functional ability, mood, stress, quality of life, dietary behaviour via 3-day food records and a modified Food Frequency Questionnaire, body composition, changes in the gut microbiome, metabolomics and cytometric parameters. Outcomes will be assessed at baseline and day 7, after 6 weeks, 12 weeks and after 6 months.Ethics and dissemination Ethical approval to process and analyse data, and to publish the results was obtained through the institutional review board of Charité-Universitätsmedizin Berlin. Results of this trial will be disseminated through peer-reviewed publications and scientific presentations.Trial registration number NCT03856190.